SIMULATION OF MULTIPLIER OPERATION IN CRITICAL APPLICATIONS - Drozd, O. V.; Vysochyna, P. V.; Dombrovskyi, V. Y.; Smishchuk, K. V.; Shalak, O. O. (Systems and Technologies, 2019)
The paper is devoted to the study of the mantissas iterative array multi-plier functioning as part of the safety-related system in case of multiple faults. Pro-cessing of mantissas is considered because safety-related systems typically receive ini-tial data from sensors, i.e. measurement results. These data are represented and pro-cessed in floating-point formats that define multiplication like the key operation be-cause they use it in the number record itself. Program models of majority multiplica-tion system and iterative array multiplier have been developed with checking systems built using various methods of on-line testing: checking, checking by inequalities and forbidden values of the product, i.e. using natural information redundancy of the prod-uct code. This redundancy is inherited by all mantissa processing results due to the key nature of the multiplication operation. The majority system and iterative array multi-plier with its checking systems in case of multiple faults were simulated. They can oc-cur in the most responsible emergency mode of the safety-related system under condi-tions of fault accumulation during prolonged normal mode. Faults are accumulated due to the lack of input data showing them. These data are typical only for the emer-gency mode of operation of the safety-related systems. As a fault, a short circuit be-tween two points of the operation element circuit in the multiplier array is considered. The simulation was conducted on a sequence of random input data with the injection of a fault between randomly selected points and the operational element. Results of simu-lation for majority system and its separate channels of multiplication, as well as itera-tive array multiplier of mantissas with complete and truncated execution of operation and residue checking system by modulo three, systems by inequality and own forbidden values of product are obtained. The trustworthiness of the results calculated by the ma-jority system under the action of multiple faults and the trustworthiness of the on-line testing methods implemented in the considered checking systems were evaluated.